2019
DOI: 10.1111/mmi.14397
|View full text |Cite
|
Sign up to set email alerts
|

Monoderm bacteria: the new frontier for type IV pilus biology

Abstract: Summary In the diverse world of bacterial pili, type IV pili (Tfp) are unique for two reasons: their multifunctionality and ubiquity. This latter feature offers an extraordinary possibility, that is, to perform comparative studies in evolutionarily distant species in order to improve our fragmentary understanding of Tfp biology. Regrettably, such potential has remained largely untapped, because, for 20 years, Tfp have only been characterised in diderm bacteria. However, recent studies of Tfp in monoderms have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 61 publications
0
39
0
Order By: Relevance
“…Type IV pili are widely detected in Gram-negative and Gram-positive bacteria, and in archaea; these participate in adhesion, twitching motility, swimming motility, natural competence for DNA uptake, and phage secretion. [49][50][51] Type IV pili include Type IVa, Type IVb, Tad/Flp, and Com pili, and archaeal flagellum (archaellum). Type IVa pili are the best Type IV pili characterized thus far.…”
Section: Type IV Pilimentioning
confidence: 99%
“…Type IV pili are widely detected in Gram-negative and Gram-positive bacteria, and in archaea; these participate in adhesion, twitching motility, swimming motility, natural competence for DNA uptake, and phage secretion. [49][50][51] Type IV pili include Type IVa, Type IVb, Tad/Flp, and Com pili, and archaeal flagellum (archaellum). Type IVa pili are the best Type IV pili characterized thus far.…”
Section: Type IV Pilimentioning
confidence: 99%
“…Together with these conserved structural features, the conservation en bloc of the genes encoding the Com pilus strongly suggests that the molecular mechanisms of filament assembly and DNA uptake are widely conserved in Firmicutes. These mechanisms, which remain poorly understood, can be advantageously studied in S. sanguinis, which has recently emerged as a monoderm T4P model (20). Actually, S. sanguinis is so far the only monoderm likely to express two distinct T4F, Com pili and retractable T4aP, which further cements it as a prime model species.…”
Section: Discussionmentioning
confidence: 99%
“…So far, Com pili have been mainly studied in two model competent species: B. subtilis and S. pneumoniae. S. sanguinis is a naturally competent species that has recently emerged as a monoderm T4F model since it expresses retractable T4aP (20). Functional analysis of S. sanguinis T4aP showed that they are dispensable for DNA uptake, which is instead mediated by Com pili since competence was abolished in a ΔcomGB mutant (21).…”
Section: Com Pili Genes Are Almost Ubiquitous In Monoderm Bacilli Inmentioning
confidence: 99%
“…Cyanobacterial T4P have been shown to play a role in twitching motility [ 5 , 29 ], metal uptake [ 30 , 31 ], biofilm formation [ 32 ], flocculation [ 33 ] and also in natural competence [ 14 , 34 ]. The filament of T4P mainly consists of the major pilin, which in cyanobacteria, is referred to as PilA1 [ 5 , 15 , 17 , 35 , 36 ]. PilA1 is exported to the periplasm via the General Secretory (Sec) pathway [ 37 ].…”
Section: The Molecular Basis Of Natural Competencementioning
confidence: 99%